DEVELOP A MINI LESSON PLAN BASED ON TBLT (TASK-BASED LANGUAGE TEACHING) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article will explore the multifaceted role of teaching aids in foreign language teaching. It will examine their theoretical underpinnings in educational psychology and second language acquisition research, analyze their practical application across different language skills (listening, speaking, reading, and writing), and evaluate the impact of technological evolution on their nature and efficacy.